2019
DOI: 10.1002/uog.20557
|View full text |Cite
|
Sign up to set email alerts
|

OC20.01: Preoperative mapping of deep infiltrating endometriosis in the posterior compartment using transvaginal strain elastography and IDEA classification

Abstract: Objectives: Severe neonatal hypoglycemia (SNH) can cause brain injury and long-term neurodevelopmental impairment. The aim of this study was to investigate the diagnostic effectiveness of ultrasound markers measured in the third trimester as predictors of SNH and determine if current practice can be improved. Methods: An unselected cohort of 6250 singleton fetuses had a universal 36 week scan in a single tertiary referral centre (2016)(2017). The variables included in the analysis were the criteria used in cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Due to scarring, they show with color Doppler only a minimal signalling. We have previously reported that infiltrating lesions of rectal endometriosis appear to be stiffer than sections of healthy intestinal wall by transvaginal strain elastosonographic examination [ 2 ] ( Figure 1 A). A strain ratio (SR) of 2.0 serves as a cut-off value for the optimal distinction.…”
mentioning
confidence: 99%
“…Due to scarring, they show with color Doppler only a minimal signalling. We have previously reported that infiltrating lesions of rectal endometriosis appear to be stiffer than sections of healthy intestinal wall by transvaginal strain elastosonographic examination [ 2 ] ( Figure 1 A). A strain ratio (SR) of 2.0 serves as a cut-off value for the optimal distinction.…”
mentioning
confidence: 99%